Coating material and preparation method thereof, positive electrode material and preparation method thereof, sodium-ion battery and power-related equipment

By using characteristic cladding on the positive electrode material of sodium ion battery, the structure of lithium titanium phosphate and doped lithium titanium phosphate is optimized, and the diffusion kinetics and stability of the positive electrode material is solved, achieving higher discharge specific capacity and cycle Stability improves electrochemical performance.

CN119208573APending Publication Date: 2024-12-27CNGR ADVANCED MATERIAL CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411381174.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The diffusion kinetics of the positive electrode material of sodium ion battery are slow, the dissolution of transition metal ion and air sensitivity lead to their unsatisfactory cycle stability. Especially in high-voltage areas, the ionic conductivity of the existing cladding layer is low, which hinders the electrochemical performance. promote.

Method used

Using a cladding layer including lithium titanium phosphate and doped lithium titanium phosphate, the diffusion kinetics of sodium ions are improved through the ratio of diffraction peak intensity and half-maximum width of XRD pattern characteristics, and it is used as a physical barrier to avoid the reaction of the positive electrode material with the electrolyte. , improve the interface stability of the material.

Benefits of technology

It significantly improves the discharge specific capacity and cyclic stability of the positive electrode material of sodium ion battery, reduces the residual alkali on the surface of the positive electrode material, reduces the gas production during the cell formation and circulation, and improves the electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208573A_ABST
    Figure CN119208573A_ABST
Patent Text Reader

Abstract

The invention discloses a coating material, a preparation method of the coating material, a positive electrode material, a preparation method of the positive electrode material, a sodium-ion battery and electric equipment. The positive electrode material comprises a substrate and a coating layer coating the surface of the substrate, wherein the XRD pattern of the coating layer comprises a first diffraction peak alpha with a diffraction angle 2 theta at 20-22 degrees and a second diffraction peak beta with a diffraction angle 2 theta at 23.0-25.3 degrees, and the ratio of the peak intensity I alpha of the first diffraction peak alpha to the half-peak width FWHM (alpha) is 3500-5500; and the ratio of the peak intensity I [beta] of the second diffraction peak [beta] to the half-peak width FWHM ([beta]) is 11000-16000. The ratio of the peak intensity and the half-peak width of the diffraction angle included in the XRD pattern of the coating layer of the sodium-ion battery positive electrode material meets the requirements, and compared with the sodium-ion battery positive electrode material which does not meet the requirements, the sodium-ion battery positive electrode material has higher specific discharge capacity and cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of positive electrode materials for sodium ion batteries, and more specifically, to coating materials and preparation methods thereof, positive electrode materials and preparation methods thereof, sodium ion batteries, and electrical equipment. Background Art

[0002] In recent years, electric vehicles, portable electric devices and energy storage stations have developed rapidly. The shortage of lithium resource raw materials and rising costs have become important issues in the development of lithium batteries. Sodium-ion battery technology has huge development potential and broad market prospects in the fields of large-scale energy storage and low-speed electric vehicles, and is considered to be a promising lithium-ion battery supplement technology.

[0003] Sodium-ion battery layered transition metal oxide materials are considered to be a promising sodium-ion battery cathode material due to their good electrochemical performance, cost, scalability and safety. However, the slow diffusion kinetics, dissolution of transition metal ions and air sensitivity of layered oxide cathode materials lead to unsatisfactory cycle stability, especially in high-voltage areas. Currently, the air and electrochemical stability of electrode materials are mainly improved by surface coating, element doping modification and electrolyte modification. Among them, coating modification can avoid corrosion caused by direct contact between active materials and electrolytes, reduce side reactions, and significantly improve the stability of the surface structure. However, the ionic conductivity of most coating layers is low, and the diffusion kinetics of surface sodium ions are hindered to a certain extent, which is not conducive to the improvement of electrochemical performance.

[0004] In view of this, this application is hereby filed. Summary of the invention

[0005] The purpose of this application is to provide a coating material and a preparation method thereof, a positive electrode material and a preparation method thereof, a sodium ion battery, and electrical equipment to improve the discharge specific capacity and cycle stability of the positive electrode material.

[0006] This application is implemented as follows:

[0007] In a first aspect, the present application provides a positive electrode material for a sodium ion battery, the positive electrode material comprising a substrate and a coating layer coated on the surface of the substrate, the XRD spectrum of the coating layer comprising: a first diffraction peak α at a diffraction angle 2θ of 20°-22° and a second diffraction peak β at a diffraction angle 2θ of 23.0°-25.3°, wherein the peak intensity I of the first diffraction peak α is α Ratio of half-peak width FWHM (α) I α / FWHM(α) is 3500-5500; the peak intensity of the second diffraction peak β is I β Ratio of half-peak width FWHM (β) I β / FWHM(β) is 11000~16000.

[0008] In an alternative embodiment, the full width at half maximum (FWHM) of the first diffraction peak α is 0.05° to 0.11°;

[0009] and / or, the FWHM of the second diffraction peak β is 0.05° to 0.08°.

[0010] In an alternative embodiment, the matrix material includes a layered oxide, and the coating material includes lithium titanium phosphate and / or doped lithium titanium phosphate.

[0011] In an alternative embodiment, the chemical general formula of the layered oxide is Na y MO2, where 0.6 < y < 1.1, and M is selected from at least one of Ni, Fe, Mn, Co, Ti, Cu, Ca, Zn, Mg, Al, Y, Ce, Sr, Sn, Ba, La, or Li;

[0012] and / or, the chemical general formula of the lithium titanium phosphate and / or doped lithium titanium phosphate is Li 1+x Ti 2-x M' x (PO4)3, where 0 ≤ x ≤ 0.5, and M' is selected from at least one of Mg, Ca, Zn, Al, Sc, Ga, In, Y, La, Zr, or Sn;

[0013] and / or, the D50 of the matrix material is 3 μm to 20 μm;

[0014] and / or, the D50 of the coating material is 50 nm to 200 nm;

[0015] and / or, the thickness of the coating layer is 140 nm to 200 nm;

[0016] and / or, the mass of the coating layer accounts for 0.3 wt% to 5 wt% of the mass of the matrix;

[0017] and / or, the mass of the residual alkali on the surface of the positive electrode material accounts for less than 0.05 wt% of the mass of the positive electrode material.

[0018] In a second aspect, the present application provides a method for preparing a positive electrode material for a sodium-ion battery as described in the foregoing embodiments. A first sintering is performed on a first mixture including the matrix material and the coating material to obtain the positive electrode material.

[0019] In an alternative embodiment, the first mixture satisfies at least one of the following conditions:

[0020] A. The mass ratio of the coating material to the matrix material in the first mixture is (0.003 to 0.05):1;

[0021] B. The maximum temperature of the first sintering is 400°C to 650°C, and the holding time at the maximum temperature is 4h to 6h;

[0022] C. The heating rate in the first sintering step is 1°C / min to 5°C / min;

[0023] D. Also includes: sanding and drying the coating layer material, and then mixing it with the base material to obtain the first mixture.

[0024] In a third aspect, the present application provides a coating material for a positive electrode material of a sodium ion battery, wherein the XRD spectrum of the coating material comprises: a first diffraction peak α at a diffraction angle 2θ of 20°-22° and a second diffraction peak β at a diffraction angle 2θ of 23.0°-25.3°, wherein the peak intensity I of the first diffraction peak α is α Ratio of half-peak width FWHM (α) I α / FWHM(α) is 3500-5500; the peak intensity of the second diffraction peak β is I β Ratio of half-peak width FWHM (β) I β / FWHM(β) is 11000~16000.

[0025] In an optional embodiment, the coating material includes lithium titanium phosphate and / or doped lithium titanium phosphate;

[0026] And / or, the D50 of the coating material is 50nm to 200nm;

[0027] And / or, the specific surface area of ​​the coating material is 3m 2 / g~15m 2 / g;

[0028] And / or, the chemical formula of the coating material is Li 1+x Ti 2-x M' x (PO4)3, wherein 0≤x≤0.5, wherein M' is selected from at least one of Mg, Ca, Zn, Al, Sc, Ga, In, Y, La, Zr or Sn;

[0029] and / or, the half-peak width of the first diffraction peak α is 0.05° to 0.11°;

[0030] And / or, the half-peak width of the second diffraction peak β is 0.05° to 0.08°.

[0031] In a fourth aspect, the present application provides a method for preparing the coating material described in the aforementioned embodiment, wherein a second mixture including a phosphorus source, a titanium source, and a lithium source is subjected to a second sintering, and the sintered product is subjected to post-treatment to obtain the coating material;

[0032] Optionally, the second mixture further comprises a source of M', wherein M' is selected from at least one of metal oxides or metal hydroxides of Mg, Ca, Zn, Al, Sc, Ga, In, Y, La, Zr or Sn;

[0033] Optionally, the second sintering includes first heating up for pre-sintering, and then heating up to a maximum temperature for solid phase sintering in an air atmosphere after the pre-sintering;

[0034] Optionally, the heating rate is 1°C / min to 5°C / min;

[0035] Optionally, the pre-firing temperature is 400° C. to 600° C., and the pre-firing time is 3 h to 5 h;

[0036] Optionally, the maximum temperature is 900° C. to 1000° C., and the insulation time at the maximum temperature is 5 h to 15 h.

[0037] In a fifth aspect, the present application provides a sodium ion battery, comprising the sodium ion battery positive electrode material described in the aforementioned embodiment.

[0038] In a sixth aspect, the present application provides an electrical device, comprising the sodium ion battery described in the aforementioned embodiment.

[0039] This application has at least the following beneficial effects:

[0040] The present application provides a sodium ion battery positive electrode material, wherein the ratio of the peak intensity and the half-peak width of the diffraction angle included in the XRD spectrum of the coating layer of the sodium ion battery positive electrode material meets the above requirements, and compared with the sodium ion battery positive electrode material that does not meet the above requirements, the sodium ion positive electrode material has higher discharge specific capacity and cycle stability.

[0041] The present application provides a coating material for a positive electrode material of a sodium ion battery, wherein the coating material comprises lithium titanium phosphate and / or doped lithium titanium phosphate, wherein the ratio of the peak intensity and the half-peak width of the diffraction angle included in the XRD spectrum of the coating material meets the above requirements, and when the lithium titanium phosphate and / or doped lithium titanium phosphate that meet the requirements are used as the coating material for the positive electrode material of the sodium ion battery, the diffusion kinetics of sodium ions can be improved while serving as a physical barrier to prevent the positive electrode material from reacting with the electrolyte, thereby improving the interface stability of the material, and ultimately improving the discharge specific capacity and cycle stability of the material.

[0042] In addition, the coating material can effectively reduce the residual alkali on the surface of the positive electrode material and reduce the gas production during the subsequent battery cell formation and cycle process. The results show that the positive electrode material coated with the coating material whose XRD spectrum includes the ratio of the peak intensity and half-peak width of the diffraction angle meets the above requirements shows significantly improved electrochemical performance in both the high voltage buckle test and the full power test, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0044] Figure 1 XRD diagram of LiTi2(PO4)3 prepared in Example 1 and Comparative Example 1;

[0045] Figure 2 The discharge specific capacity of button cells assembled with the positive electrode materials in Comparative Example 1, Comparative Example 2 and Example 1 at a voltage range of 2.0 to 4.2 V at 0.1C and 0.2C rates, and the capacity attenuation after 50 cycles at a rate of 1C;

[0046] Figure 3 The capacity retention rate of the fully electric soft-pack battery assembled with the positive electrode materials prepared in Comparative Example 2 and Example 1 after 600 cycles at a voltage range of 2.0 to 4.25 V and a rate of 0.5C / 1C;

[0047] Figure 4 The SEM images of LiTi2(PO4)3 before sand grinding (left picture) and nano-LiTi2(PO4)3 after sand grinding for 6 hours (right picture) in Example 1;

[0048] Figure 5 SEM images of NMTMA@LTP(μm)-550℃ in Example 8 (left picture) and NMTMA@1wt%LTP-550℃ in Example 1 (right picture);

[0049] Figure 6 The cross-sectional SEM image (left) and EDS image (right) of NMTMA@1wt%LTP-550℃ in Example 1;

[0050] Figure 7 The figure is a comparison of the fluidity of the slurry of the positive electrode materials prepared in Example 1 and Comparative Example 2 during the preparation of the full electrode sheet. DETAILED DESCRIPTION

[0051] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0052] The present application provides a positive electrode material for a sodium ion battery, wherein the positive electrode material comprises a substrate and a coating layer coated on the surface of the substrate, wherein the XRD spectrum of the coating layer comprises: a first diffraction peak α at a diffraction angle 2θ of 20°-22° and a second diffraction peak β at a diffraction angle 2θ of 23.0°-25.3°, wherein the peak intensity I α Ratio of half-peak width FWHM (α) I α / FWHM(α) is 3500-5500; the peak intensity of the second diffraction peak β is I β Ratio of half-peak width FWHM (β) I β / FWHM(β) is 11000~16000.

[0053] The present application provides a sodium ion battery positive electrode material, wherein the ratio of the peak intensity and the half-peak width of the diffraction angle included in the XRD spectrum of the coating layer of the sodium ion battery positive electrode material meets the above requirements, and compared with the sodium ion battery positive electrode material that does not meet the above requirements, the sodium ion positive electrode material has higher discharge specific capacity and cycle stability.

[0054] In the XRD spectrum of the coating layer of the positive electrode material of the sodium ion battery, the first diffraction peak α is the diffraction peak of the (104) crystal plane of the coating layer; α / FWHM(α) is 3500-5500, specifically 3500, 4000, 4500, 5000, 5500 or any value between 3500 and 5500; the second diffraction peak β is the diffraction peak of the (113) crystal plane of the coating layer, I β / FWHM(β) is 11000-16000, and specifically can be 11000, 12000, 13000, 14000, 15000, 16000 or any value between 11000 and 16000.

[0055] In an optional embodiment, the half-peak width of the first diffraction peak α is 0.05° to 0.11°, specifically 0.05°, 0.06°, 0.07°, 0.08°, 0.09°, 0.10°, 0.11° or any value between 0.05° and 0.11°;

[0056] And / or, the half-peak width of the second diffraction peak β is 0.05° to 0.08°, specifically, it can be 0.05°, 0.06°, 0.07°, 0.08° or any value between 0.05° and 0.08°.

[0057] The half-width of the diffraction peak reflects the grain size and microstructure of the crystal. For a coating layer that meets the above requirements, a smaller half-width means that the crystal is more complete.

[0058] In an alternative embodiment, the matrix material comprises a layered oxide, and the coating material comprises lithium titanium phosphate and / or doped lithium titanium phosphate.

[0059] The coating material comprises lithium titanium phosphate and / or doped lithium titanium phosphate. The ratio of the peak intensity to the full-width at half-maximum of the diffraction angles included in the XRD pattern satisfies the above requirements for lithium titanium phosphate or doped lithium titanium phosphate. The TiO6 octahedra and PO4 tetrahedra are interconnected by sharing corners to form a three-dimensional ion diffusion channel, which has excellent three-dimensional framework structure stability, strong covalent bonds, and excellent ionic conductivity, facilitating the improvement of the sodium ion diffusion rate. Compared with lithium titanium phosphate or doped lithium titanium phosphate that does not meet the above XRD pattern requirements, on the one hand, the local distortion and defects generated by the TiO6 octahedra in the Na + diffusion path are improved, showing better ion diffusion ability; on the other hand, the configuration / connection of the TiO6 octahedra and PO4 tetrahedra is more perfect, showing higher structural stability. The sodium ion cathode material containing it has higher initial efficiency, discharge specific capacity, and cycle stability.

[0060] Lithium titanium phosphate and / or doped lithium titanium phosphate can improve the diffusion kinetics of sodium ions while acting as a physical barrier to prevent the reaction between the cathode material and the electrolyte, improve the interfacial stability of the material, and ultimately increase the discharge specific capacity and cycle stability of the material. In addition, the coating material can effectively reduce the residual alkali on the surface of the cathode material, reduce the gas generation during the subsequent formation and cycling of the battery cells, enabling the cathode material to exhibit significantly improved electrochemical performance in both high-voltage charge-discharge tests and full-cell tests, and having good application prospects.

[0061] In an alternative embodiment, the chemical general formula of the layered oxide is Na y MO2, where 0.6 < y < 1.1, and M is selected from at least one of Ni, Fe, Mn, Co, Ti, Cu, Ca, Zn, Mg, Al, Y, Ce, Sr, Sn, Ba, La, or Li; the diffusion kinetics of the layered oxide cathode material is slow, the transition metal ions dissolve, and the air sensitivity results in unsatisfactory cycle stability. When the ratio of the peak intensity to the full-width at half-maximum of the diffraction angles included in the XRD pattern of the cathode material coating layer satisfies the above requirements, the ion transport ability and structural stability of the layered oxide cathode material can be effectively improved.

[0062] In an alternative embodiment, the chemical general formula of the lithium titanium phosphate and / or doped lithium titanium phosphate is Li 1+x Ti 2- x M' x(PO4)3, wherein 0≤x≤0.5, wherein M' is selected from at least one of Mg, Ca, Zn, Al, Sc, Ga, In, Y, La, Zr or Sn; the structure is derived from the structure of LiTi2(PO4)3, Ti is partially replaced by M', and additional Li atoms are inserted, and then other elements are doped as needed to improve the comprehensive performance of the positive electrode material.

[0063] In an optional embodiment, D50 of the base material is 3 μm to 20 μm; specifically, it can be 3 μm, 4 μm, 5 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm or any value between 3 μm and 20 μm.

[0064] If the particle size of the matrix material is too large, the path of the sodium ion deintercalation process will be too long, thereby increasing the difficulty of sodium ion deintercalation; if the particle size of the matrix material is too small, it may reduce the stability of the positive electrode material.

[0065] In an optional embodiment, D50 of the coating layer material is 50nm to 200nm, specifically can be 50nm, 60nm, 70nm, 90nm, 100nm, 120nm, 140nm, 150nm, 170nm, 180nm, 190nm, 200nm or any value between 50nm and 200nm.

[0066] When the D50 of the coating layer material is within a suitable range, the ultrafine powder has a higher reactivity and is more easily activated and adsorbed on the surface of the matrix particles, forming a uniform coating layer after subsequent low-temperature sintering.

[0067] In an optional embodiment, the thickness of the coating layer is 140 nm to 200 nm; specifically, it can be 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm or any value between 140 nm and 200 nm.

[0068] If the coating layer is too thin, the uniformity of the coating will be reduced, making the isolation effect of the coating layer on the substrate and the electrolyte worse. At the same time, it will be difficult to reduce the residual alkali on the surface and the effect of reducing gas production will not be obvious, resulting in reduced effects on improving the material's discharge capacity and cycle stability. If the coating layer is too thick, the capacity of the positive electrode material will be reduced.

[0069] In an optional embodiment, the mass of the coating layer accounts for 0.3wt% to 5wt% of the mass of the substrate; specifically, it can be 0.3wt%, 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt% or any value between 0.3wt% and 5wt%.

[0070] Under the same conditions, if the mass proportion of the coating layer is too low and the thickness of the coating layer is too small, the uniformity of the coating will be reduced, making the isolation effect of the coating layer on the substrate and the electrolyte worse, and it will be difficult to reduce the residual alkali on the surface and the effect of reducing gas production is not obvious, resulting in reduced effects on improving the material's discharge capacity and cycle stability; if the mass proportion of the coating layer is too high, the capacity of the positive electrode material will be reduced.

[0071] In an optional embodiment, the residual alkali mass on the surface of the positive electrode material accounts for less than 0.05wt% of the mass of the positive electrode material. The positive electrode material of the sodium ion battery of the present application has low residual alkali, which can improve its air stability.

[0072] The present application also provides a method for preparing the positive electrode material for a sodium ion battery described in the aforementioned embodiment, comprising performing a first sintering on a first mixture including the matrix material and the coating layer material to obtain the positive electrode material.

[0073] In an optional embodiment, the first mixture satisfies at least one of the following conditions:

[0074] A. The mass ratio of the coating layer material to the matrix material in the first mixture is (0.003-0.05):1; specifically, it can be 0.003:1, 0.005:1, 0.01:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1 or any value between (0.003-0.05):1; reasonably setting the mass ratio of lithium titanium phosphate and the positive electrode material is conducive to obtaining a coating layer of a preset thickness.

[0075] B. The maximum temperature of the first sintering is 400℃~650℃, specifically 400℃, 450℃, 500℃, 550℃, 600℃, 650℃ or any value between 400℃ and 650℃; the holding time at the maximum temperature is 4h~6h, specifically 4h, 5h, 6h or any value between 4h and 6h; the atmosphere is an oxygen-containing atmosphere, such as air and oxygen; the first sintering condition will affect the bonding force between the coating layer and the substrate, and thus affect the stability of the material structure, and also affect the material capacity, rate performance, etc.

[0076] C. The heating rate in the first sintering step is 1°C / min to 5°C / min; specifically, it can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min or any value between 1°C / min and 5°C / min.

[0077] D. Also includes: sand grinding and drying the coating layer material, and then mixing it with the base material to obtain the first mixture. The embodiment of the present application adopts wet sand grinding, sand grinding the lithium titanium phosphate to a particle size that meets the requirements and then drying, the purpose of drying is to remove the solvent mixed in the lithium titanium phosphate, the drying temperature can be 60℃~80℃, and the drying time can be 6h~8h.

[0078] In an optional embodiment, in wet sand milling, the ball-to-material ratio is 1:3, the solid content of the abrasive is 50wt% to 80wt%, the sand milling time is 4h to 6h, and the sand milling is sieved through 500 mesh; the sand milling conditions can ball mill the micron-level lithium titanium phosphate to the nanometer level, and water or alcohol and other solvents can be added during the sand milling process to improve the dispersion effect of the lithium titanium phosphate. Reducing the particle size of the coating layer material is conducive to forming a uniform and dense coating layer on the surface of the base material.

[0079] The positive electrode material matrix in the first mixture can be prepared by the following method: y The molar ratio of the elements in the MO2 chemical formula is obtained by weighing a metal compound containing M and a sodium source, stirring and mixing them evenly, calcining and cooling to room temperature, and then crushing and sieving to obtain a powdery layered positive electrode material matrix.

[0080] Among them, in the process of preparing the positive electrode material matrix, the metal compound containing M includes one or more of metal oxides, metal hydroxides, and metal carbonates containing M elements; the sodium source is one or more of sodium carbonate, sodium hydroxide, or sodium bicarbonate; M is selected from one or more of Ni, Fe, Mn, Co, Ti, Cu, Ca, Zn, Mg, Al, Y, Ce, Sr, Sn, Ba, La, and Li. The metal compound containing M and the sodium source corresponding to the preparation of the positive electrode material matrix are placed in a high-speed mixer and fully mixed to obtain a third mixture, in which the molar ratio of sodium to M can be between 0.6 and 1.1; the high-speed mixer speed is 200 to 2000 rpm, and the mixing time is 20 to 40 minutes. The third mixture is placed in a calcination device for calcination, and the conditions are: heating rate 1 to 5°C / min, pre-calcination temperature 400 to 600°C, maximum temperature 900 to 1000°C, high temperature time 5 to 15h, and calcination atmosphere is one or more of air or oxygen. The calcined material is crushed and screened to obtain the desired positive electrode material matrix. The crushing method can be high-speed universal crusher crushing or jaw crusher followed by air flow mill crushing. The microscopic morphology of the obtained positive electrode material matrix can be polycrystalline or single crystal particles.

[0081] The present application also provides a coating material for a sodium ion battery positive electrode material, wherein the XRD spectrum of the coating material comprises: a first diffraction peak α at a diffraction angle 2θ of 20°-22° and a second diffraction peak β at a diffraction angle 2θ of 23.0°-25.3°, wherein the peak intensity Iα Ratio of half-peak width FWHM (α) I α / FWHM(α) is 3500-5500; the peak intensity of the second diffraction peak β is I β Ratio of half-peak width FWHM (β) I β / FWHM(β) is 11000~16000.

[0082] The present application provides a coating material for a positive electrode material of a sodium ion battery. The ratio of the peak intensity and the half-peak width of the diffraction angle included in the XRD spectrum of the coating material meets the above requirements. When the coating material that meets the requirements is used as a coating material for a positive electrode material of a sodium ion battery, it can improve the diffusion kinetics of sodium ions while serving as a physical barrier to prevent the positive electrode material from reacting with the electrolyte, thereby improving the interface stability of the material, and ultimately improving the discharge specific capacity and cycle stability of the material.

[0083] In addition, the coating material can effectively reduce the residual alkali on the surface of the positive electrode material and reduce the gas production during the subsequent battery cell formation and cycle process. The results show that the positive electrode material coated with the coating material whose XRD spectrum meets the above requirements shows significantly improved electrochemical performance in both high voltage buckle test and full power test, and has good application prospects.

[0084] In an optional embodiment, the coating material includes lithium titanium phosphate and / or doped lithium titanium phosphate;

[0085] In an optional embodiment, the D50 of the coating material is 50nm to 200nm; specifically, it can be 50nm, 80nm, 110nm, 140nm, 170nm, 200nm or any value between 50nm and 200nm; using nano-scale lithium titanium phosphate with a D50 of 50nm to 200nm as a raw material for coating modification is conducive to forming a uniform coating layer compared to micron-scale lithium titanium phosphate coating, which effectively improves the sodium ion diffusion rate while inhibiting the side reaction between the positive electrode material and the electrolyte, and improving its interface stability, thereby improving the discharge specific capacity and cycle stability of the material.

[0086] In an optional embodiment, the specific surface area of ​​the coating material is 3m 2 / g~15m 2 / g, specifically 3m 2 / g, 6m 2 / g, 9m 2 / g, 12m 2 / g, 15m 2 / g or 3m 2 / g~15m 2 / g, the coating material with a large specific surface area usually exhibits higher surface energy and surface activity, making it easy to spread evenly on the outer surface of the substrate particles to form a coating layer.

[0087] In an optional embodiment, the chemical formula of the coating material is Li 1+x Ti 2-x M' x (PO4)3, wherein 0≤x≤0.5, wherein M' is selected from at least one of Mg, Ca, Zn, Al, Sc, Ga, In, Y, La, Zr or Sn;

[0088] In an optional embodiment, the half-peak width of the first diffraction peak α is 0.05° to 0.11°;

[0089] In an optional embodiment, the half-peak width of the second diffraction peak β is 0.05° to 0.08°.

[0090] The embodiment of the present application also provides a method for preparing the coating material described in the aforementioned embodiment, wherein a second mixture including a phosphorus source, a titanium source, and a lithium source is subjected to a second sintering, and the sintered product is subjected to a post-treatment to obtain the coating material;

[0091] Among them, the phosphorus source can be one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium phosphate, phosphoric acid or hypophosphorous acid; the titanium source can be one or more of titanium dioxide, tetrabutyl titanate, titanium isopropoxide, titanium sulfate or titanyl sulfate; the lithium source can be one or more of lithium carbonate, lithium hydroxide or lithium nitrate. The second mixture can be obtained by mixing the phosphorus source, titanium source and lithium source in a food processor according to the ratio of LiTi2(PO4)3. In some embodiments, the phosphorus source, titanium source and lithium source can be weighed in a stoichiometric ratio of 3:2:1 of phosphorus, titanium and lithium elements, or the lithium source and phosphorus source can be excessive to make up for the loss during calcination, for example, an excess of 1% to 5%. After the second sintering, the second sintered material can be preliminarily crushed, sieved and wet sanded, and then sieved and dried.

[0092] In an optional embodiment, the second mixture further includes an M' source, and M' is selected from at least one of metal oxides or metal hydroxides of Mg, Ca, Zn, Al, Sc, Ga, In, Y, La, Zr or Sn, so that a doped coating material can be prepared.

[0093] In an optional embodiment, the second sintering includes first heating up for pre-sintering, and then heating up to a maximum temperature for solid phase sintering in an air atmosphere after pre-sintering;

[0094] Optionally, the heating rate is 1°C / min to 5°C / min;

[0095] Optionally, the pre-firing temperature is 400° C. to 600° C., and the pre-firing time is 3 h to 5 h;

[0096] Optionally, the maximum temperature is 900° C. to 1000° C., and the insulation time at the maximum temperature is 5 h to 15 h.

[0097] Limiting the raw material ratio and sintering process of the coating material is conducive to obtaining the coating material whose XRD spectrum meets the above requirements.

[0098] An embodiment of the present application also provides a sodium ion battery, comprising the sodium ion battery positive electrode material described in the aforementioned embodiment.

[0099] An embodiment of the present application also provides an electrical device, including the sodium ion battery described in the aforementioned embodiment.

[0100] The features and performance of the present application are further described in detail below in conjunction with the examples. The test methods for testing the products involved in the following examples and comparative examples are described as follows:

[0101] 1. XRD was measured by X-ray diffractometer, and the reference standard GA / T 2079-2023 was used for determination. The crystal structure of each sample in this application was tested by Rigaku SmartLab 9kW X-ray diffractometer (XRD, Cu Kα), with a scanning range of 5-80° and a scanning rate of 8° / min;

[0102] 2. The particle size is tested by Malvern 3000 laser particle size analyzer, with reference to GB / T 19077-2016;

[0103] 3. EDS uses an X-ray energy spectrum scanner to measure the metal components in the positive electrode material particles;

[0104] 4. The thickness of the coating layer can be observed through the SEM image taken after argon ion polishing.

[0105] Example 1

[0106] This embodiment provides a method for preparing a positive electrode material for a sodium ion battery, comprising the following steps:

[0107] (1) Preparation of target LiTi2(PO4)3: ① Li2CO3, TiO2, and NH4H2PO4 were weighed in a high-speed mixer at a molar ratio of 1.03:2:3.15 for lithium, titanium, and phosphorus, and mixed evenly, wherein Li2CO3 was in excess of 3% relative to the stoichiometric ratio and NH4H2PO4 was in excess of 5% relative to the stoichiometric ratio to compensate for the volatilization of lithium and phosphorus during the calcination process. ② Pre-sinter at 550℃ for 4h at a heating rate of 1℃ / min, heat to 950℃, sinter and hold for 12h, solid-phase sintering in air atmosphere, and then cool naturally. Use a universal grinder to crush the obtained material and pass it through a 100-mesh sieve, then sand grind and sieve to obtain the final required coating material, wherein the ball-to-material ratio of sand grinding is 1:3, the solid content of the abrasive is 70wt%, the sand grinding time is 6h, and after collection, vacuum drying for 8h, crushing and sieving through a 500-mesh sieve to obtain a nano-scale coating material with a D50 of 87nm. Its XRD results are shown in Figure 1 The crystal structure data are: I(α) / FWHM(α), i.e. I(104) / FWHM(104), is 5344, and the half-peak width of the (104) crystal plane is 0.09°; I(β) / FWHM(β), i.e. I(113) / FWHM(113), is 15015, and the half-peak width of the (113) crystal plane is 0.065°.

[0108] (2) Preparation of NMTMA cathode material matrix: ① Select the binary precursor Ni with a D50 of 3.8 μm 0.50 Mn 0.50 (OH)2 and Na2CO3, TiO2, MgO, Al2O3 were placed in a high-speed mixer and fully mixed, wherein n(Na) / n(TM) = 1.03. ② Solid-phase sintering was carried out in an air atmosphere at a heating rate of 1°C / min and a sintering temperature of 950°C for 12 hours, and then the temperature was naturally lowered. The obtained material was crushed using a jet mill and sieved through a 400-mesh sieve to obtain Na 0.92 Ni 0.40 Mn 0.40 Ti 0.12 Mg 0.04 Al 0.04 O2.

[0109] (3) LiTi2(PO4)3 (0.6128 g) powder was added to the obtained NMTMA (60 g) matrix for coating and modification. The mixture was fully mixed using a food processor, and then solid-phase sintered for 6 hours in an air atmosphere at a heating rate of 2°C / min and a sintering temperature of 550°C, followed by natural cooling. The obtained material was sieved through a 400-mesh sieve to obtain the target LiTi2(PO4)3-coated sodium ion battery positive electrode material (NMTMA@1wt%LTP-550°C).

[0110] Example 2

[0111] This embodiment provides a method for preparing a positive electrode material for a sodium ion battery. The difference from Example 1 is that the heating rate during the sintering process of LiTi2(PO4)3 is changed from 1°C / min to 3°C / min, and the target LiTi2(PO4)3-coated positive electrode material for a sodium ion battery (NMTMA@LTP-3°C / min) is obtained. The crystal structure data are: I(α) / FWHM(α), i.e., I(104) / FWHM(104), is 3856, and the half-peak width of the (104) crystal plane is 0.104°; I(β) / FWHM(β), i.e., I(113) / FWHM(113), is 11875, and the half-peak width of the (113) crystal plane is 0.08°.

[0112] Example 3

[0113] This embodiment provides a method for preparing a positive electrode material for a sodium ion battery. The difference from Example 1 is that the coating amount of LiTi2(PO4)3 is adjusted from 1wt% to 3wt% to obtain a target LiTi2(PO4)3-coated sodium ion battery positive electrode material (NMTMA@3wt%LTP-550℃).

[0114] Example 4

[0115] This embodiment provides a method for preparing a positive electrode material for a sodium ion battery. On the basis of Embodiment 1, the base material coated with LiTi2(PO4)3 is replaced with NFMCM. The specific steps are as follows:

[0116] (1) Preparation of target LiTi2(PO4)3: same as step (1) of Example 1.

[0117] (2) Preparation of NFMCM cathode material matrix: ① Select the ternary precursor Ni with a D50 of 3.8 μm 0.50 Mn 0.50 (OH)2 and Na2CO3, Fe2O3, MgO, CaCO3 were placed in a high-speed mixer and fully mixed, wherein n(Na) / n(TM) = 1.03. ② Solid-phase sintering was carried out in an air atmosphere at a heating rate of 1°C / min and a sintering temperature of 950°C for 12 hours, and then the temperature was naturally lowered. The obtained material was crushed using a jet mill and sieved through a 400-mesh sieve to obtain Na 0.92 Ni 0.32 Fe 0.12 Mn 0.48 Mg 0.04 Ca 0.04 O2.

[0118] (3) 1 wt% target nano-LiTi2(PO4)3 (0.6128 g) powder was added to the obtained NFMCM (60 g) matrix for coating and modification. The mixture was fully mixed using a food processor, and then solid-phase sintered for 6 hours in an air atmosphere at a heating rate of 2°C / min and a sintering temperature of 550°C, followed by natural cooling. The obtained material was sieved through a 400-mesh sieve to obtain the target LiTi2(PO4)3-coated sodium ion battery positive electrode material (NFMCM@1wt%LTP-550°C).

[0119] Example 5

[0120] This embodiment provides a method for preparing a positive electrode material for a sodium ion battery. On the basis of Embodiment 1, Al is used to replace part of Ti to obtain Li 1.3 Ti 1.7 Al 0.3 (PO4)3 coating material, the specific steps are as follows:

[0121] (1)Li 1.3 Ti 1.7 Al 0.3 Preparation of (PO4)3: ① Weigh Li2CO3, Al2O3, TiO2, and NH4H2PO4 in a molar ratio of lithium, aluminum, titanium, and phosphorus of 1.34:0.3:1.7:3.15 and mix them evenly in a high-speed mixer, wherein Li2CO3 is in excess of 3% relative to the stoichiometric ratio and NH4H2PO4 is in excess of 5% relative to the stoichiometric ratio to compensate for the volatilization of lithium and phosphorus during calcination. ② Pre-sinter at 550°C for 4h at a heating rate of 1°C / min, heat to 950°C, sinter and hold for 12h, carry out solid-phase sintering in an air atmosphere throughout the process, and then cool naturally. Use a universal grinder to initially crush the obtained material and pass it through a 100-mesh sieve, then sand grind and sieve to obtain the final required coating material, wherein the ball-to-material ratio of sand grinding is 1:3, and the solid content of the abrasive is 70wt%. After collection, vacuum dry for 8h, crush and sieve through a 500-mesh sieve to obtain a nano-scale coating material with a D50 of 115nm. Its crystal structure data are as follows: I(α) / FWHM(α), i.e. I(104) / FWHM(104), is 4254, and the half-width of the (104) crystal plane is 0.08°; I(β) / FWHM(β), i.e. I(113) / FWHM(113), is 12500, and the half-width of the (113) crystal plane is 0.071°.

[0122] (2) Preparation of NMTMA positive electrode material matrix: same as step (2) of Example 1.

[0123] (3) 1wt% Li 1.3 Ti 1.7 Al 0.3(PO4)3 (0.9134 g) powder was added to the obtained NMTMA (60 g) matrix for coating and modification. The mixture was fully mixed using a food processor, and then solid-phase sintering was performed in an air atmosphere at a heating rate of 2 °C / min and a sintering temperature of 550 °C for 6 h, followed by natural cooling. The obtained material was sieved through a 400-mesh sieve to obtain the target Li 1.3 Ti 1.7 Al 0.3 (PO4)3 coated sodium ion battery positive electrode material (NMTMA@1wt% LAT P-550℃).

[0124] Example 6

[0125] This embodiment provides a method for preparing a positive electrode material for a sodium ion battery. On the basis of Embodiment 1, Y is used to replace part of Ti to obtain Li 1.4 Ti 1.6 Y 0.4 (PO4)3 coating material, the specific steps are as follows:

[0126] (1)Li 1.4 Ti 1.6 Y 0.4 Preparation of (PO4)3: ① Weigh Li2CO3, Y(OH)3, TiO2, and NH4H2PO4 in a molar ratio of lithium, yttrium, titanium, and phosphorus of 1.44:0.4:1.6:3.15 and mix them evenly in a high-speed mixer, wherein Li2CO3 is in excess of 3% relative to the stoichiometric ratio and NH4H2PO4 is in excess of 5% relative to the stoichiometric ratio to compensate for the volatilization of lithium and phosphorus during calcination. ② Pre-sinter at 550°C for 4h at a heating rate of 1°C / min, heat to 950°C, sinter and hold for 12h, carry out solid-phase sintering in an air atmosphere throughout the process, and cool naturally. Use a universal grinder to initially crush the obtained material and pass it through a 100-mesh sieve, then sand grind and sieve to obtain the final required coating material, wherein the ball-to-material ratio of sand grinding is 1:3, and the solid content of the abrasive is 70wt%. After collection, vacuum dry for 8h, crush and sieve through a 500-mesh sieve to obtain a nano-scale coating material with a D50 of 126nm. Its crystal structure data are as follows: I(α) / FWHM(α), i.e. I(104) / FWHM(104), is 3866, and the half-width of the (104) crystal plane is 0.085°; I(β) / FWHM(β), i.e. I(113) / FWHM(113), is 11579, and the half-width of the (113) crystal plane is 0.078°.

[0127] (2) Preparation of NMTMA positive electrode material matrix: same as step (2) of Example 1.

[0128] (3) 1wt% Li 1.4 Ti 1.6 Y0.4 (PO4)3 (0.9505 g) powder was added to the obtained NMTMA (60 g) matrix for coating and modification. The mixture was fully mixed using a food processor, and then solid-phase sintering was performed in an air atmosphere at a heating rate of 2 °C / min and a sintering temperature of 550 °C for 6 h, followed by natural cooling. The obtained material was sieved through a 400-mesh sieve to obtain the target Li 1.4 Ti 1.6 Y 0.4 (PO4)3-coated sodium-ion battery positive electrode material (NMTMA@1wt%LYTP-550℃).

[0129] Example 7

[0130] This embodiment provides a method for preparing a positive electrode material for a sodium ion battery. On the basis of Example 1, the sintering temperature of the LiTi2(PO4)3 coating in step (3) is adjusted from 550°C to 700°C to obtain a LiTi2(PO4)3-coated sodium ion battery positive electrode material (NMTMA@1wt%LTP-700°C).

[0131] Example 8

[0132] This embodiment provides a method for preparing a positive electrode material for a sodium ion battery, using a micron-sized LiTi2(PO4)3 coating material that has not been sanded and refined to coat the base material of Embodiment 1, and the specific steps are as follows:

[0133] (1) Preparation of target LiTi2(PO4)3: ① Li2CO3, TiO2, and NH4H2PO4 were weighed in a high-speed mixer according to the molar ratio of lithium, titanium, and phosphorus of 1.03:2:3.15, and mixed evenly, wherein Li2CO3 was 3% in excess relative to the stoichiometric ratio, and NH4H2PO4 was 5% in excess relative to the stoichiometric ratio to compensate for the volatilization of lithium and phosphorus during the calcination process. ② Pre-sintering at 550℃ for 4h at a heating rate of 1℃ / min, heating to 950℃, sintering and holding time for 12h, solid-phase sintering was carried out in an air atmosphere throughout the process, and then the temperature was naturally lowered. The obtained material was initially crushed using a universal crusher and passed through a 500-mesh sieve to obtain a micron-grade lithium titanium phosphate powder with a D50 of 10μm.

[0134] (2) Preparation of NMTMA positive electrode material matrix: same as step (2) of Example 1.

[0135] (3) Micron-sized LiTi2(PO4)3 (0.6128 g) powder was added to the obtained NMTMA (60 g) matrix for coating and modification. The mixture was fully mixed using a food processor, and then solid-phase sintered for 6 h in an air atmosphere at a heating rate of 2°C / min and a sintering temperature of 550°C, followed by natural cooling. The obtained material was sieved through a 400-mesh sieve to obtain a sodium ion battery positive electrode material coated with lithium titanium phosphate (NMTMA@LTP (μm)-550°C).

[0136] Comparative Example 1

[0137] This comparative example provides a method for preparing a positive electrode material for a sodium ion battery, which specifically comprises the following steps:

[0138] (1) Preparation of LiTi2(PO4)3: ① Disperse tetrabutyl titanate in anhydrous propanol and stir for 10 to 20 minutes until the titanium source is dissolved to form a transparent uniform solution. Then add deionized water drop by drop and stir for 4 hours to hydrolyze the titanium source to obtain a milky white suspension. ② Add ammonium dihydrogen phosphate and lithium acetate dihydrate and react under magnetic stirring for 2 to 5 hours. Transfer the mixed suspension to a reactor and hydrothermally react at 180°C for 12 hours. Filter, wash and dry the obtained material. Use a universal grinder to perform preliminary crushing and pass through a 100-mesh sieve. Then sand grind and sieve to obtain the final desired coating material. The ball-to-material ratio of sand grinding is 1:3, the solid content of the abrasive is 70wt%, and the sand grinding time is 6 hours. After collection, vacuum dry for 8 hours to obtain LiTi2(PO4)3 coating material. Its XRD results are shown in Figure 1 The crystal structure data are: I(α) / FWHM(α), i.e. I(104) / FWHM(104), is 325; I(β) / FWHM(β), i.e. I(113) / FWHM(113), is 744.

[0139] (2) Preparation of NMTMA positive electrode material matrix: same as step (2) of Example 1.

[0140] (3) LiTi2(PO4)3 (0.6128 g) powder was added to the obtained NMTMA (60 g) matrix for coating and modification. The mixture was fully mixed using a food processor, and then solid-phase sintered for 6 hours in an air atmosphere at a heating rate of 2°C / min and a sintering temperature of 550°C. The resulting material was sieved through a 400-mesh sieve to obtain a LiTi2(PO4)3-coated sodium-layer oxygen positive electrode material (NMTMA@1wt%LTP-550°C).

[0141] Comparative Example 2

[0142] This comparative example provides a Na 0.92 Ni 0.40 Mn0.40 Ti 0.12 Mg 0.04 Al 0.04 O2, the preparation method of which is the same as step (2) of Example 1.

[0143] Comparative Example 3

[0144] This comparative example provides a method for preparing a positive electrode material for a sodium ion battery, comprising the following steps:

[0145] (1) Preparation of target NaTi2(PO4)3: ① Weigh Na2CO3, TiO2, and NH4H2PO4 according to the stoichiometric ratio of sodium, titanium, and phosphorus of 1.03:2:3.15 and mix them evenly in a high-speed mixer, wherein Na2CO3 is in excess of 3% relative to the stoichiometric ratio and NH4H2PO4 is in excess of 5% relative to the stoichiometric ratio to compensate for the volatilization of sodium and phosphorus during calcination. ② The solid-phase sintering was carried out in an air atmosphere for 12 hours with a heating rate of 1°C / min, pre-sintering at 550°C for 4 hours, and a sintering temperature of 980°C, followed by natural cooling. The obtained material was initially crushed using a universal grinder and passed through a 100-mesh sieve, and then sieved through sand milling to obtain the final required coating material, wherein the ball-to-material ratio of sand milling was 1:3, the solid content of the abrasive was 70wt%, the sand milling time was 6 hours, and after collection, it was vacuum dried for 8 hours, crushed and sieved through a 500-mesh sieve to obtain a nano-grade sodium titanium phosphate powder with a D50 of 74nm.

[0146] (2) Preparation of NMTMA positive electrode material matrix: same as step (2) of Example 1.

[0147] (3) NaTi2(PO4)3 (0.6382 g) powder was added to the obtained NMTMA (60 g) matrix for coating and modification. The mixture was fully mixed using a food processor, and then solid-phase sintered for 6 h in an air atmosphere at a heating rate of 2°C / min and a sintering temperature of 550°C, followed by natural cooling. The obtained material was sieved through a 400-mesh sieve to obtain a NaTi2(PO4)3-coated sodium ion battery positive electrode material (NMTMA@1wt%NTP-550°C).

[0148] Comparative Example 4

[0149] This comparative example provides a Na 0.92 Ni 0.32 Fe 0.12 Mn 0.48 Mg 0.04 Ca 0.04 O2, whose preparation method is the same as step (2) of Example 4.

[0150] The positive electrode materials obtained in each embodiment and comparative example were tested, and pole pieces were independently prepared and assembled into sodium ion button batteries. The specific operation steps are as follows:

[0151] (1) pH value and residual alkali test: Using anhydrous ethanol as the solvent, the NaOH content on the surface of the positive electrode material was measured by potentiometric titration.

[0152] (2) Preparation of positive electrode sheets: The prepared positive electrode material, conductive agent (Super P), and binder (polyvinylidene fluoride PVDF) are placed in a weighing bottle at a mass ratio of 85:10:5, and an appropriate amount of dispersing solvent (N-methylpyrrolidone NMP) is added and stirred to form a uniform slurry, which is then coated on an aluminum foil, followed by drying, rolling, and slicing to form the positive electrode sheets required for button batteries; NMTMA@1wt%LTP-550℃ (or NMTMA matrix), conductive agent CNT (carbon nanotube conductive slurry), conductive agent SP (carbon black) and binder PVDF (polyvinylidene fluoride) are dispersed in NMP (N-methylpyrrolidone) at a mass ratio of 95.0:1.0:1.5:2.5, and the slurry is obtained after stirring and dispersion. The slurry is coated on both surfaces of the aluminum foil, and rolled to a compaction density of 3.0g / cm3. Finally, the positive electrode sheet is die-cut into a round or square positive electrode sheet as the positive electrode sheet of a sodium ion button battery or a soft-pack battery.

[0153] (3) Sodium ion button cell assembly test: All batteries use CR2032 button cells. The battery is assembled in the order of positive electrode shell, gasket, positive electrode sheet prepared in the above steps, diaphragm, electrolyte, Na metal negative electrode, gasket, spring, and negative electrode shell. It is then placed on a button cell sealing machine and kept at a certain pressure for about 30 seconds. After being removed and left to stand for a period of time, the electrochemical performance test is performed on a blue battery test system. The cut-off voltage range is 2.0 to 4.2 V, the test rate is 0.1C activation for 2 cycles, then 0.2C activation for 2 cycles, and finally 1C cycle for 50 cycles. The test temperature is 25±1°C.

[0154] (4) Assembling sodium ion soft pack batteries: The main material hard carbon, the conductive agent SP (carbon black), the binder SBR (styrene butadiene rubber) and the binder CMC (carboxymethyl cellulose) are dispersed in deionized water at a mass ratio of 94:2.5:2.0:1.0, and the slurry is obtained after stirring and dispersion. The slurry is coated on aluminum foil / copper foil and rolled to a compaction density of 0.9 g / cm3. The negative electrode sheet is then die-cut into a square negative electrode sheet; the solvent PC (ethylene carbonate) and EMC (ethyl methyl carbonate) are stirred and mixed at a mass ratio of 3:7, and sodium hexafluorophosphate is slowly added to a molar concentration of 1 mol / L, add additives FEC (methylene disulfonate) 2wt%, VC (vinyl carbonate) 1wt%, PST (propylene-1,3-sultone) 0.2wt%, and stir evenly to obtain an electrolyte; stack the positive electrode sheet, separator, and negative electrode sheet obtained above in order, weld the positive and negative electrode ears, and put them into a semi-sealed aluminum-plastic film after fixing, and then after top sealing and side sealing, transfer to 85℃ vacuum conditions for drying for 48h, bake until the moisture is less than 300ppm, then inject the electrolyte, and then pre-seal, and then set aside at 40-50℃ for 20-36h.

[0155] The results of the buckling test on the positive electrode materials prepared in Examples 1 to 8 and Comparative Examples 1 to 4 are shown in Table 1.

[0156] Table 1: Performance of buckle test of Examples 1 to 8 and Comparative Examples 1 to 4

[0157]

[0158]

[0159] The results of the positive electrode materials prepared in Example 1 and Comparative Example 2 in the full-electric soft-pack battery test are shown in Table 2.

[0160] Table 2 Test performance of all-electric soft-pack batteries of Example 1 and Comparative Example 2

[0161]

[0162] The test results of Examples 1 to 8 and Comparative Examples 1 to 4 are shown in Tables 1 to 2 and Figures 1 to 7 The target nano-LiTi2(PO4)3 coated NMTMA positive electrode material in Example 1 has significantly improved the discharge specific capacity and 50-cycle capacity retention rate when applied to button batteries. The maximum capacity at 1C can reach 149.32mAh / g, and the 50-cycle capacity retention rate is increased to 98.58%. When applied to all-electric soft-pack batteries, the capacity retention rate after 600 cycles is increased from 79.14% to 90.93% while the capacity remains basically unchanged. Figure 2It can be seen from Comparative Example 1 and Example 1 that the degree of crystallization integrity of the LiTi2(PO4)3 coating material has a great influence on the 1C cycle capacity of the battery. The battery with a coating layer that does not meet the XRD conditions has a significantly lower discharge capacity than the target LiTi2(PO4)3 coated battery. It can be seen from Example 4 and Comparative Example 4 that the performance of the target LiTi2(PO4)3 coated NFMCM positive electrode material has also been significantly improved. Figure 3 It can be seen that the materials described in Example 1 and Comparative Example 2 are respectively applied to all-electric soft-pack batteries, and the target nano-LiTi2(PO4)3 coating significantly improves the capacity retention rate of the NMT MA positive electrode material.

[0163] from Figure 4 It can be seen that under 10K magnification, the particle size of LiTi2(PO4)3 becomes significantly smaller after sand grinding for 6 hours. Figure 5 It can be seen that compared with the coating of unsanded micron-sized lithium titanium phosphate, the target nano-LiTi2(PO4)3 obtained after sanding has a more uniform coating on the surface of the NMTMA matrix, and there are no fine particles on the surface. It can also be seen from Examples 1 and 8 that coating with nano-sized lithium titanium phosphate is beneficial to the improvement of the capacity of the positive electrode material, and appropriately reducing the powder particle size is beneficial to the activation of the coating material and adsorption on the surface of the matrix material, forming a uniform and dense protective barrier in the subsequent sintering.

[0164] Figure 6 The left picture in the middle is a cross-sectional SEM image of the single crystal particle coated with nano-LiTi2(PO4)3 in Example 1. It can be seen that the coating layer is 140nm to 200nm thick and the coating is uniform. The right picture is the EDS result of the slice, in which the Ti content of the matrix is ​​significantly higher than that of the coating layer. 4+ The covalent bond between TM and lattice oxygen is strengthened, stabilizing the structure of the material; while the less Ti element in the coating layer can promote the ion diffusion dynamics while reducing the destruction of the crystal structure caused by the inherent local distortion of the TiO6 octahedron, making the positive electrode material have better structural stability.

[0165] The results of testing the pH value and residual hydroxide content of the positive electrode materials prepared in Examples 1 to 3 and Comparative Example 2 are shown in Table 3.

[0166] Table 3 pH value and residual hydroxide content of Examples 1 to 3 and Comparative Example 2

[0167] Sample No. pH <![CDATA[OH - wt%]]> Example 1 NMTMA@1wt%LTP-550℃ 12.02 0.046 Example 2 NMTMA@LTP-3℃ / min 12.09 0.048 Example 3 NMTMA@3wt%LTP-550℃ 12.11 0.045 Comparative Example 2 NMTMA matrix 12.13 0.142

[0168] It can be seen from Table 3 that the target nano-LiTi2(PO4)3 coated layered oxide Na 0.92 Ni 0.40 Mn 0.40 Ti0.12 Mg 0.0 4Al 0.04 The residual alkali of Examples 1 to 3 of O2 is less than 0.05wt%, while the residual alkali of NMTMA matrix in Comparative Example 2 is significantly higher than 0.05wt%, reaching 0.142wt%. Figure 7 From the slurry state of the positive electrode materials described in Example 1 and Comparative Example 2, it can be seen that the uncoated NMTMA matrix slurry is relatively viscous, while the target nano-LiTi2(PO4)3 coating can effectively improve the gel phenomenon of the positive electrode material during the homogenization process, which is attributed to the reduction of residual alkali on the surface of the positive electrode material.

[0169] The embodiments of the present application can effectively reduce the residual alkali on the surface of sodium-electrolyte layered oxides, thereby improving the gelation phenomenon in the all-electric preparation homogenization process and the gas production phenomenon in the subsequent circulation process.

[0170] It can be seen from the above test results that no matter it is a high-voltage button battery test or a high-voltage full-electric soft-pack battery test, the target lithium titanium phosphate or doped lithium titanium phosphate-coated sodium-layer oxygen positive electrode material shows significantly improved electrochemical performance and has good application prospects.

[0171] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A sodium ion battery positive electrode material, characterized in that: The positive electrode material comprises a substrate and a coating layer coated on the surface of the substrate, wherein the XRD spectrum of the coating layer comprises: a first diffraction peak α at a diffraction angle 2θ of 20°-22° and a second diffraction peak β at a diffraction angle 2θ of 23.0°-25.3°, wherein the peak intensity I α Ratio of half-peak width FWHM (α) I α / FWHM(α) is 3500-5500; the peak intensity of the second diffraction peak β is I β Ratio of half-peak width FWHM (β) I β / FWHM(β) is 11000~16000.

2. The sodium ion battery positive electrode material according to claim 1, characterized in that The half-peak width of the first diffraction peak α is 0.05° to 0.11°; And / or, the half-peak width of the second diffraction peak β is 0.05° to 0.08°.

3. The sodium ion battery positive electrode material according to claim 1, characterized in that The matrix material comprises layered oxide, and the coating layer material comprises lithium titanium phosphate and / or doped lithium titanium phosphate.

4. The sodium ion battery positive electrode material according to claim 3, characterized in that The chemical general formula of the layered oxide is Na y MO2, where 0.6 < y < 1.1, and M is selected from at least one of Ni, Fe, Mn, Co, Ti, Cu, Ca, Zn, Mg, Al, Y, Ce, Sr, Sn, Ba, La or Li; And / or, the chemical formula of the lithium titanium phosphate and / or doped lithium titanium phosphate is Li 1+x Ti 2-x M' x (PO4)3, wherein 0≤x≤0.5, wherein M' is selected from at least one of Mg, Ca, Zn, Al, Sc, Ga, In, Y, La, Zr or Sn; And / or, the D50 of the base material is 3 μm to 20 μm; And / or, the D50 of the coating layer material is 50nm to 200nm; And / or, the coating layer has a thickness of 140 nm to 200 nm; and / or, the mass of the coating layer accounts for 0.3wt% to 5wt% of the mass of the substrate; And / or, the mass of residual alkali on the surface of the positive electrode material accounts for less than 0.05wt% of the mass of the positive electrode material.

5. A method for preparing a positive electrode material for a sodium ion battery according to any one of claims 1 to 4, characterized in that: The first mixture including the base material and the coating layer material is first sintered to obtain the positive electrode material.

6. The method for preparing a positive electrode material for a sodium ion battery according to claim 5, characterized in that: The first mixture satisfies at least one of the following conditions: A. The mass ratio of the coating material to the matrix material in the first mixture is (0.003-0.05):1; B. The maximum temperature of the first sintering is 400°C to 650°C, and the holding time at the maximum temperature is 4h to 6h; C. The heating rate in the first sintering step is 1°C / min to 5°C / min; D. Also includes: sanding and drying the coating layer material, and then mixing it with the base material to obtain the first mixture.

7. A coating material for a sodium ion battery positive electrode material, characterized in that: The XRD spectrum of the coating material includes: a first diffraction peak α at a diffraction angle 2θ of 20°-22° and a second diffraction peak β at a diffraction angle 2θ of 23.0°-25.3°, wherein the peak intensity I α Ratio of half-peak width FWHM (α) I α / FWHM(α) is 3500-5500; the peak intensity of the second diffraction peak β is I β Ratio of half-peak width FWHM (β) I β / FWHM(β) is 11000~16000.

8. The coating material according to claim 7, characterized in that: The D50 of the coating material is 50nm to 200nm; And / or, the coating material includes lithium titanium phosphate and / or doped lithium titanium phosphate; And / or, the specific surface area of ​​the coating material is 3m 2 / g~15m 2 / g; And / or, the chemical formula of the coating material is Li 1+x Ti 2-x M' x (PO4)3, wherein 0≤x≤0.5, wherein M' is selected from at least one of Mg, Ca, Zn, Al, Sc, Ga, In, Y, La, Zr or Sn; and / or, the half-peak width of the first diffraction peak α is 0.05° to 0.11°; And / or, the half-peak width of the second diffraction peak β is 0.05° to 0.08°.

9. A method for preparing a coating material according to claim 7 or 8, characterized in that: Performing a second sintering on a second mixture including a phosphorus source, a titanium source, and a lithium source, and performing a post-treatment on the sintered product to obtain the coating material; Optionally, the second mixture further comprises a source of M', wherein M' is selected from at least one of metal oxides or metal hydroxides of Mg, Ca, Zn, Al, Sc, Ga, In, Y, La, Zr or Sn; Optionally, the second sintering includes first heating up for pre-sintering, and then heating up to a maximum temperature for solid phase sintering in an air atmosphere after the pre-sintering; Optionally, the heating rate is 1°C / min to 5°C / min; Optionally, the pre-firing temperature is 400° C. to 600° C., and the pre-firing time is 3 h to 5 h; Optionally, the maximum temperature is 900° C. to 1000° C., and the insulation time at the maximum temperature is 5 h to 15 h.

10. A sodium ion battery, characterized in that: The invention comprises the sodium ion battery positive electrode material according to any one of claims 1 to 4.

11. An electrical equipment, characterized in that: Including the sodium ion battery as described in claim 9.